Epigenetic Mechanisms in Environmental Adaptation: A Conceptual Review of Molecular Regulatory Systems - Diana Widhi Rachmawati; Dian Pariska; Nisah Ayu Siregar (Exacta: Journal of Pure and Fundamental Research, 2026)
Environmental change imposes escalating selective pressures that demand rapid yet reversible adaptive responses across biological systems. This study presents a non-empirical conceptual review that synthesizes epigenetic mechanisms as a hierarchical and cross-kingdom molecular regulatory architecture linking environmental stimuli to phenotypic plasticity and ecological memory. Drawing upon comparative systems mapping and structured narrative synthesis, the analysis integrates DNA methylation dynamics, histone modification codes, chromatin remodeling complexes, non-coding RNA networks, and metabolic–immune feedback circuits into a unified explanatory framework. The findings demonstrate that adaptive regulation operates through recursive feedback loops that recalibrate transcriptional states under fluctuating environmental conditions, enabling graded transitions from short-term plasticity to stabilized ecological memory. Cross-domain triangulation across plants, animals, fungi, and insects reveals conserved structural motifs underlying stress adaptation despite taxonomic divergence. The proposed model refines evolutionary interpretations of adaptation by embedding energetic constraints, immune modulation, and developmental plasticity within epigenetic regulatory systems. This integrative framework offers conceptual clarity, cross-kingdom generalizability, and predictive coherence, providing a structured platform for future empirical validation and computational modeling of adaptive resilience in the context of global environmental change.